Practical Self-Defense for Elementary School Students - Alif, Muhammad Nur; Muhtar, Tatang (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
This study was aimed at determining the effect of practical self-defense learning on elementary school students’ self-efficacy. The method used was the experimental research method. The research design used was Randomized Pretest-Postest Control Group Design. The instrument used was a self-efficacy questionnaire. The research location was located in Sumedang. The population is 4, 5, and 6 grade students in elementary school. The results showed that practical self-defense learning had a positive effect on students' self-efficacy; the students who received self-defense learning and had the concept of practical self-defense understanding showed better self-efficacy results compared to students who did not get learning and understanding of the concept of practical self-defense. However, the results of self-efficacy testing on female students did not experience a significant increase. Age in female students seems to be a determinant factor in the results of the test that had been conducted.